2016
DOI: 10.1016/j.hlc.2016.02.021
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Radiation Protection Solutions for the Staff in the Cardiac Catheterisation Laboratory

Abstract: Adverse health effects of radiation exposure to staff in cardiac catheterisation laboratories have been well documented in the literature. Examples include increased risk of cataracts as well as possible malignancies. These risks can be partly mitigated by reducing scatter radiation exposure to staff during diagnostic and interventional cardiac procedures. There are currently commercially available radiation protection tools, including radioprotective caps, gloves, eyewear, thyroid collars, aprons, mounted shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…The use of lead-free radiation-attenuating latex gloves can reduce radiation by 58%. 47 The best way to protect the hands is to shield them from the primary beam. Single-use unleaded radiation-protective gloves are recommended.…”
Section: Glovesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of lead-free radiation-attenuating latex gloves can reduce radiation by 58%. 47 The best way to protect the hands is to shield them from the primary beam. Single-use unleaded radiation-protective gloves are recommended.…”
Section: Glovesmentioning
confidence: 99%
“…Studies have shown that using lead glasses lowers the dose of lens radiation by 98%. [46][47][48] The use of non-lead glasses reduces the radiation dose by 36% compared to 87% with lead glasses. A lead acrylic face mask that protects the corners the eyes has been shown to reduce radiation exposure by 97%.…”
Section: Eyewearmentioning
confidence: 99%
“…The development of cardiac catheterization procedures has been associated with increasing numbers of radiation‐induced diseases in the medical staff, ranging from “benign” subcapsular cataracts to a presumed higher risk of malignancies . Interventional cardiologists and room staff are exposed to two main sources of radiation: X‐ray tube leakage and scatter radiation from the patient . Other than procedural characteristics such as frame rate reduction or minimizing cineangiography, various protective tools have been developed (lead apron, leaded glass mobile panel, RADPAD® drapes) with proven radiation protection.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Interventional cardiologists and room staff are exposed to two main sources of radiation: X-ray tube leakage and scatter radiation from the patient. 3,4 Other than procedural characteristics such as frame rate reduction or minimizing cineangiography, various protective tools have been developed (lead apron, leaded glass mobile panel, RADPAD ® drapes) with proven radiation protection. They are however dependent on the staff behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This two-piece lead garment typically weighs 15-40 pounds, which the surgeon supports on their shoulders and waist. Lead garments can be worn for up to 12 hours a day, leading to short-term musculoskeletal fatigue and longitudinal injury primarily to the neck, lower back, hip, knee and ankle [3].…”
mentioning
confidence: 99%